Behavior of beef cows grazing topographically rugged native range is influenced by mineral delivery system - N.A. Sproul; J.W. Bolte; D.R. Linden; R.A. Kreikemeier; L.A. Pacheco; M.D. Thomas; James J. Higgins; K. C. Olson; James S. Drouillard; John R. Jaeger (Kansas Agricultural Experiment Station Research Reports, 2008)
Poor grazing distribution is a major problem on rangelands of the western United States. Grazing animals tend to congregate in areas near water, shade, and level terrain. These areas typically become overgrazed, while less preferred areas of pasture remain undergrazed. Solutions to localized overgrazing include cross-fencing and water development; however, most land managers are unwilling to bear the expense associated with these strategies. Most types of supplements, including mineral supplements, have potential to lure cattle into under-utilized areas of range and pasture. Cows spend up to 40% of their time within 650 yards of self-fed supplements, but relationships between terrain use, mineral supplement delivery method, and mineral supplement consumption remain unclear.
Keywords: Cattlemen' s Day; 2008; Kansas Agricultural Experiment Station contribution; no. 08-212-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 995; Beef; Cattle; Grazing solutions; Mineral Supplements